Effect of varying light intensity on maximal power production and selected metabolic variables - Ohkuwa, T.; Itoh, H.; Yamamoto, T.; Yanagi, H.; Yamazaki, Y.; Akimaru, T. (Archives of Physiology and Biochemistry, 2001)
This study was designed to examine the effect of exposure to two levels of light intensity (bright; 5000 lux, dim; 50 lux) prior to supramaximal cycle exercise on performance and metabolic alterations. The exercise was performed after bright and dim light exposure for 90 minutes. Ten male long-distance runners volunteered to take part in the study. They performed 45-sec supramaximal exercise using a cycle ergometer in a 500-lux. Mean power output was measured during the exercise. Lactate and ammonia in the blood and epinephrine and norepinephrine concentrations in plasma were measured at rest immediately after bright and dim light exposures and after the exercise. Bright and dim light exposure priors to exercise did not significantly affect the power output during the exercise. Blood glucose concentration immediately after exercise and plasma epinephrine during the resting period were significantly lower after bright light exposure compared with dim light exposure (p < 0.05). No significant difference was found in blood lactate, ammonia, or plasma norepinephrine levels after exercise following bright and dim light exposures. This study demonstrated that bright light stimulation prior to supramaximal exercise decreases glucose and epinephrine levels, but is not related to physical performance.